Innovation Design and Development of PET Plastic Waste Processing Machines by Extruder Method - Hadi Pranoto; Zainal Arifin; Henry Carles (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2020)
According to the Ministry of Environment (KLH), Indonesia's average population produces 189 thousand tons of garbage per day. Of this amount, 15% is plastic waste or 28.4 thousand tons of plastic waste per day. The famous handling of plastic waste is 3R (Reduce, Reuse, Recycle). Reduce is reducing the purchase or use of goods made from plastic, especially disposable items. Reuse is the repeated use of plastic-based items.  Recycle is recycling goods made of plastic.  The method used in this design study is to use SolidWorks software by combining the literature study VDI221 to obtain a variant of the design results that will be used. The study results do a plastic bench machine that is integrated to produce plastic seeds, which are PET-shaped, which are extruded in a device that has been brewed. From the results of the design in the data processing and design specifications of the PET plastic waste-processing machine with the extruder method, the construction consists of several units, namely, Shredder unit, Extruder unit, Cutter unit, and Machine frame. The shredder unit serves to destroy plastic waste that is still intact in pieces before being processed in the extruder unit. The extruder unit functions to melt PET waste to be extruded using a screw. The cutter unit operates to cut processed extrusion waste into pellet granules. The engine frame is used to support the entire engine unit. The results of the Plastic Waste Extruder Machine design process with an Autodesk inventor are summarized in the following specifications: machine dimensions are 1625 mm long, 300mm wide, and 1325mm high; screw extruder uses a metering screw type with a diameter of 50.8mm (2 inches) with a length: diameter ratio of 20: 1, so the screw length is 1016mm, estimated throughput rate = 84 lb/h (42kg / h), the motor used is 5.5 PK (4 KW) with a rotation speed of 1450.